Corporate tax responsibility in Africa: Insight from Nigeria. (2nd April 2020) - Amaeshi, Kenneth; Adi, Bongo; Ikiebey, Godson; McCulloch, Neil
ABSTRACT: This study explores how small business owners in Africa talk about their tax responsibility, using Nigeria as a case study. Data were collated through interviews, focus group sessions, and online chats. The study identifies two main types of tax responsibility talks amongst these business owners: (1) duty-based and (2) right-based discourses. The duty-based talks see taxation primarily as the citizens' responsibility to governments, which should always be fulfilled unconditionally, while right-based talks see taxation primarily as the government's responsibility to citizens, which should be fulfilled first, in order for the government to earn the trust of citizens for higher tax compliance. Further analyses reveal that these talks are anchored on four common discursive themes – i.e. socioeconomic development, and legal, moral, and philanthropic themes, which business owners respond to in different ways. The paper argues that understanding these diverse responses will help tax regulators respond to taxpayers' attitudes effectively.